Гумористичні меми як технокультурний інструмент громадянської стійкості в умовах російського вторгнення в Україну (Серія: Історія. Політологія, 2025)
Стаття досліджує роль гумористичних мемів як технокультурних інструментів громадянської стійкості в умовах повномасштабного російського вторгнення в Україну. Аналізується трансформація традиційних форм гумору у цифрові меми, які стали новою технологією комунікації та соціальної мобілізації. На основі контент-аналізу мемів, поширених через цифрові платформи протягом першого року війни, досліджуються функції гумору як інструменту подолання соціокультурної травми. Гумористичні тематичні меми  розглядаються як технокультурне явище, що поєднує традиційні функції сміху (катарсис, консолідація, опір) з можливостями цифрових технологій (миттєве поширення, вірусність, мультимедійність). Особлива увага приділяється ролі так званого «гумору шибеника», репрезентації колективної ідентичності через меми та створенню контрнаративів проти російської пропаганди. Демонструється, що меми функціонують як інструменти самоорганізованої соціальної інженерії, формуючи горизонтальні мережі підтримки та колективної стійкості в умовах екзистенційної загрози. This article examines the role of humorous memes as technocultural instruments of civic resilience during the full-scale Russian invasion of Ukraine. The study analyzes the transformation of traditional forms of humor into digital memes, which have become a new technology of communication and social mobilization. Based on content analysis of memes distributed through digital platforms (X.com, Telegram, TikTok, Facebook, Instagram) during the first year of the war, the research explores the functions of humor as an instrument for overcoming sociocultural trauma.Humorous memes are examined as a technocultural phenomenon that combines traditional functions of laughter (catharsis, consolidation, resistance) with the capabilities of digital technologies (instant dissemination, virality, multimedia, interactivity). The article applies P. Sztompka's theory of social trauma, which identifies four characteristics of traumatic events: suddenness and speed of changes, totality and radical nature of changes, exogeneity, and negative character. The Russian invasion of Ukraine corresponds to these characteristics, layering upon painful historical processes of denationalization, creating a phenomenon of multilayered frozen trauma.Special attention is devoted to the role of «gallows humor» as a survival mechanism in conditions of existential threat. Drawing on Z. Freud's psychoanalytic theory and P. Wong's research on humor during wartime, the study demonstrates how memes function as a compensatory mechanism for releasing negative psychic energy. The research shows that the intensity of tragic events directly correlates with the generation of humorous content, providing therapeutic relief to society.The article analyzes memes as instruments of collective identity representation through the «friend-enemy» dichotomy. Linguistic constructs such as «rashists», «palianytsia», and visual symbols became markers of oppositional identity, functioning as «cultural software» according to L. Shifman, that creates shared semantic systems. Digital platforms enabled identity formation not through official propaganda but organically, through mass participatory engagement in creating and disseminating cultural content.Memes are examined as counter-narratives against Russian propaganda in the context of «semantic war». By ridiculing the enemy's geopolitical ambitions and imperial narratives, Ukrainians created humorous variations that deconstructed the image of Russia as a «great power» through simple but effective visual images. The study demonstrates how the object of fear, becoming an object of laughter, loses its capacity to intimidate and control through fear.The research conceptualizes memes as instruments of self-organized social engineering – a spontaneous, decentralized process where millions of individual actors simultaneously act as creators and consumers of cultural content. This process is based on voluntary participation, emotional solidarity, and shared cultural codes. Digital platforms created infrastructure for mass self-organization of society, where horizontal anonymous communities provided emotional support through shared cultural understanding.The study concludes that humorous memes acquired a new function as instruments for overcoming sociocultural trauma alongside their traditional entertainment role. The instantaneity of creation, collective authorship, and horizontal dissemination provided them with effectiveness unavailable to traditional forms of humor. Memes became a synthesis of technology and culture, a hybrid phenomenon that demonstrates constructive potential of digital algorithms in forming horizontal networks of support and collective resilience under conditions of existential threat.